Perception of environmental risk level among trainee-teachers: Investigation on effectiveness of teacher education programme - Sudeshna Lahiri; Biswajit Samaddar (Journal of Environment and Sustainability Education, 2026)
It is important to investigate the understanding of environmental risks among the trainee-teachers who are going to play a crucial role in shaping attitudes and behaviours among school students. The present article investigates the level of perception of environmental risk among trainee-teachers from teacher training institutions located in Kolkata, India, to examine its association with the nature of studentship. A Perception of Environmental Risk Level scale (PERLS) was administered on 150 trainee-teachers to measure three main areas of risk factors i.e., Environmental issues; Environmental pollutants, and Environmental pollutants’ effects. Thus, obtained data is subjected to Chi-Square Tests of Independence to find out the association between categorical variables (Nature of studentship x Perception of environmental risk level). To ascertain further about the associations, Phi Significance and Crammer’s V significance also been computed. Inspite of taking environmental risks seriously, a substantial proportion perceived no or low risk across the three dimensions: environmental issues (84.1%), environmental pollutants (81.0%), and effects of environmental pollutants (73.0%). Significant associations were observed between the nature of studentship and perception of environmental risk levels, with varying strengths as indicated by Phi and Cramer’s V values. The findings suggest that perception of environmental risk reflects an individual’s understanding of the urgency and importance of environment protection. The teacher education curricula should be time-appropriate to make trainee-teachers aware of environmental risks.  Incorporating the field-based and experiential learning may enhance trainee-teachers’ understanding of environmental issues, pollutants, and their effects to prepare informed and responsible future educators.